From Falling Behind to Catching Up : A Country Economic Memorandum for Malawi - Record, Richard (Washington, DC: World Bank, 2017)
This book aims to improve readers’ understanding of the puzzle of Malawi’s development performance and identify ways for the country to achieve robust growth and stay on a stable growth path that helps the poor. The book places a strong emphasis on assessing Malawi’s growth experience since independence from a comparative international perspective. This book first discusses Malawi’s macroeconomic situation and challenges in fiscal management, reviewing and drawing lessons from the instability, slippages, and shocks experienced since independence. Second, it explores the current state of agricultural markets, given the critical role of this sector in poverty reduction. Third, looking at the factors that may constrain higher growth in the future, challenges in private sector development and job creation are discussed. Building on the analysis of challenges, the book concludes with a summary of policy recommendations to help Malawi to begin catching up with its peers.